THE INFLUENCE OF AGRICULTURAL HOLDINGS ON THE NATURAL ENVIRONMENT - Kagan, Adam (Economics of Agriculture, 2013)
Agriculture is the production field, which depends on the condition of the natural environment because it uses the natural processes of growth and reproduction of living organisms. The agriculture itself also affects the environment. The effects of this interaction, both positive and negative, are additionally shaped by the social, political, economic, technical and technological surroundings. The factors determining the agricultures impact on a macro scale on the environment may, however, by brought down and subordinated to the main constituents, namely: the size of human population, demand for agricultural raw materials, the applied production technology (classical IPAT equation) and agro-climatic conditions. Based on the available forecasts and materials the potential directions and effects of constituents of the equation were analysed at the global level. However, establishing the environmental performance of a given agricultural holding and agriculture at the local level requires a different methodological approach. The article presents the method for measuring an agricultural holdings individual impact on the environment in the form of one indicator synthetic measure.